VARIASI BAHASA PADA CHANNEL YOUTUBE KRISTIAN B. HANSEN HIDUP 7 HARI BERSAMA SUKU DAYAK IBAN DI SUNGAI UTIK (KAJIAN SOSIOLINGUISTIK) - Hadi Saputro, Asda; Fitriani, Yessi; Hetilaniar, Hetilaniar (Universitas PGRI Palembang, 2023)
The purpose of this study was conducted to reveal language variations in terms of speakers used in everyday life, identify language variations used in social interactions, and identify language variations in reflecting the culture of the Iban Dayak tribe in Sungai Utik. The research method uses data collection techniques using documentation techniques and the data used is content analysis. The result of this research is that there are variations in the forms of dialect, idiolect, and sociolect. There were 9 dialect variations, 13 idiolect variations, and 8 sociolect variations that were observed. Then there is a social function in social interaction that reflects culture in Kristian's YouTube video channel b. Hansen lived 7 days with the Iban Dayak tribe on the Utik River. Keyword: Dayak Iban Language Variations, Sociolinguistics and Social Interaction